Recent advances in the use of Polyamide-based materials for the automotive industry - Kondo, Marcel Yuzo [UNESP]; Montagna, Larissa Stieven; de Melo Morgado, Guilherme Ferreira; de Castilho, André Luiz Guimarães [UNESP]; dos Santos Batista, Larissa Anne Pereira; Botelho, Edson Cocchieri [UNESP]; Costa, Michelle Leali [UNESP]; Passador, Fabio Roberto; Rezende, Mirabel Cerqueira; Ribeiro, Marcos Valério [UNESP] (FapUNIFESP (SciELO), 2022)
Polyamide (PA) is a well-known and researched thermoplastic due to its excellent mechanical and physical properties, making it developed in the automotive sector, suitable for lighter vehicles, and, consequently, lower fuel consumption. This review manuscript presents the applications of PA-based materials in the manufacture of vehicle parts, with a description of their processing, a discussion about their thermal properties and the crystallization of polymer structure, the challenges of machining PA-based composite materials, and the feasibility of recyclability. This work aims to revise literature about the use of polyamide 6 (PA6), polyamide 66 (PA66), and polyamide 12 (PA12) and their composites reinforced with fiberglass (FG) and carbon fiber (CF) focused on the potential that these materials have as alternative materials for the automotive industry.
Keywords: automotive industry; carbon fiber; composites; polyamide